Pengaruh Motivasi, Kepuasan Kerja dan Disiplin Kerja Terhadap Kinerja Pada Pegawai Dinas Pendidikan Kabupaten Labuhanbatu Utara - Masitah Pane, Sjahril Effendy Pasaribu, Zulaspan Tupti (Journal Economy and Currency Study (JECS), 2022)
The background of this research is the decline in performance in the education office of North Labuhanbatu Regency, which is thought to be caused by motivation, job satisfaction and work discipline factors. The purpose of this study was to determine and analyze the effect of motivation, job satisfaction and work discipline on the performance of the employees of the Education Office of North Labuhanbatu Regency. The approach used in this study is an associative approach. The population in this study was the Education Office of North Labuhanbatu Regency as many as 43 employees. While the sample in this study using probability sampling or sampling saturated as many as 43 employees. The data collection technique in this study used a questionnaire technique by distributing questionnaires. The data analysis technique in this study uses Multiple Linear Regression Test, Hypothesis Testing (t Test and F Test), and Coefficient of Determination. The results of this study prove that the direct influence of motivation, job satisfaction and work discipline has a positive and significant effect on employee performance at the Education Office of North Labuhanbatu Regency.